Atypical phenotype associated with reported GCK exon 10 deletions: clinical judgement is needed alongside appropriate genetic investigations. Issue 8 (16th July 2013) - Thanabalasingham, G.; Kaur, K.; Talbot, F.; Colclough, K.; Mathews, A.; Taylor, J.; Ellard, S.; Owen, K. R.
Abstract Background Maturity‐onset diabetes of the young (MODY) caused by heterozygous mutations in the glucokinase (GCK) gene typically presents with lifelong, stable, mild fasting hyperglycaemia. With the exception of pregnancy, patients with GCK‐MODY usually do not require pharmacological therapy. We report two unrelated patients whose initial genetic test results indicated a deletion of GCK exon 10, but whose clinical phenotypes were not typical of GCK‐MODY. Case reports In case 1, the patient was hyperglycaemic at diagnosis (glucose > 30 mmol/l) and elevated glucose levels > 10 mmol/l persisted after withdrawal of insulin therapy. The patient in case 2 was also hyperglycaemic at diagnosis [HbA1c > 86 mmol/mol (10%)], which improved with the introduction of oral hypoglycaemic agents. These clinical features were not consistent with GCK‐MODY. Both patients had a single nucleotide variant that prevented multiplex ligation‐dependent probe analysis, which generated a false positive result of a GCK exon 10 deletion. Conclusion False positive genetic results in these two unrelated cases were attributable to the presence of a rare single nucleotide variant that prevented ligation of the probe in the multiplex ligation‐dependent probe analysis kit used and falsely indicated deletion of exon 10 within GCK. Both cases had clinical features that did not tally with the typical GCK‐MODY phenotype. These cases emphasize the need to interpret the results of definitive genetic tests within the specific clinical context. Increased medical sequencing is likely to lead to more reports of novel mutations of uncertain significance. If genetic investigations do not agree with the clinical picture, clinicians should exercise caution when making therapeutic changes based on these results.